Legal Protection for Disadvantaged Heirs Arising from an Unlawfully Executed Deed of Gift (A Case Study of Supreme Court Decision No. 3013 K/Pdt/2022) - Siti Rahma Febrisa (Authentica: Private Law Journal, 2025)
The Land Deed Official, hereinafter referred to as PPAT, is a public official authorized to create authentic deeds concerning certain legal acts related to land rights or ownership rights over condominium units. One of the obligations of the PPAT is to draft Grant Deeds (Akta Hibah). A grant (hibah) is the transfer of ownership of property by an individual to another party gratuitously, without any compensation from the recipient, and is executed during the lifetime of the grantor. Legal protection for heirs who suffer losses due to grant deeds made unlawfully is a critical issue. This study addresses two main problems: first, the form of legal protection for heirs disadvantaged by unlawfully made grant deeds; and second, the validity of grant agreements in light of the Supreme Court Decision Number 1298 K/Pdt/2019. The research employs a juridical-normative legal method using the Statute Approach and Conceptual Approach. The results indicate that legal protection for heirs harmed by unlawful grant deeds is fulfilled through judicial decisions declaring such grant deeds invalid and legally void, and ordering the defendant to return the granted property. Regarding the validity of grant agreements, based on Supreme Court Decision Number 3013 K/Pdt/2022, the subjective requirements under Article 1320 of the Indonesian Civil Code (KUH Perdata) are not met. Specifically, the consensus of the parties involved in the agreement is legally defective if it is obtained through coercion, mistake, or fraud.